2016
DOI: 10.14814/phy2.13059
|View full text |Cite
|
Sign up to set email alerts
|

Functional respiratory imaging, regional strain, and expiratory time constants at three levels of positive end expiratory pressure in an ex vivo pig model

Abstract: Heterogeneity in regional end expiratory lung volume (EELV) may lead to variations in regional strain (ε). High ε levels have been associated with ventilator‐associated lung injury (VALI). While both whole lung and regional EELV may be affected by changes in positive end‐expiratory pressure (PEEP), regional variations are not revealed by conventional respiratory system measurements. Differential rates of deflation of adjacent lung units due to regional variation in expiratory time constants (τ E) may create lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Our study shows the physiological influence of different PEEP levels on regional airflow limitations. These data are in line with current animal experiments, demonstrating that whole lung measures of strain do not accurately represent regional pulmonary mechanics [ 40 ]. Furthermore, Pulletz et al demonstrated different time constants measured by EIT in patients with ARDS, comparable to the example given in Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Our study shows the physiological influence of different PEEP levels on regional airflow limitations. These data are in line with current animal experiments, demonstrating that whole lung measures of strain do not accurately represent regional pulmonary mechanics [ 40 ]. Furthermore, Pulletz et al demonstrated different time constants measured by EIT in patients with ARDS, comparable to the example given in Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Nowadays, applied biomechanical research has moved into the direction of medical and patient-specific applications; thus the coupling between clinical images and computational modeling can play a fundamental role in this regard. Several examples of commercially available simulation-based services can be mentioned: Medis [ 3 ] and HeartFlow [ 4 ] use CFD as diagnostic tool for Fractional Flow Reserve (FRR) by means of angio-based and CT-based images, respectively, while from a treatment perspective FluidDA [ 5 ] and FEops [ 6 , 7 ] developed commercial tools to support clinicians in respiratory diseases cases and in TAVI applications. Lastly, SIMULIA created an integrative predictive biophysical model of the human heart to extract clinical parameters and guide device design and treatment planning in cardiac diseases [ 8 ].…”
Section: Introductionmentioning
confidence: 99%